الحماية الدولية للعلامات التجارية وفقا لاتفاق مدريد للتسجيل الدولي للعلامات التجارية لعام 1891 - بوترعة، شمامة (جامعة زيان عاشور بالجلفة, 2023)
إن وجود نظام دولي فعال لتسجيل العلامات التجارية يلعب دورا حيوي في حماية هذه العلامات وتعزيز التنمية الاقتصادية والمنافسة المشروعة على الصعيدين الوطني والدولي، بحيث لا تنحصر حماية مثل هذه العلامات ضمن أراضي الدولة التي سجلت فيها، إنا تمتد لتشمل العديد من الدول على الصعيد الدولي. ومن هنا جاء اتفاق مدريد للتسجيل الدولي للعلامات التجارية لعام 1891، والذي ارتكز في أحكامه على اتفاقية باريس لحماية الملكية الصناعية، ليوفر إمكانية الحصول على حماية العلامات التجارية في مختلف الدول المتعاقدة، عن طريق إيداع طلب دولي واحد لدى المكتب الدولي التابع لمنظمة " الويبو"، والذي يتولى تسجيلها ونشر تلك التسجيلات، وتبليغها للأطراف المتعاقدة، ويل هذا الطلب محل مجموعة كاملة من الإجراءات والشكليات في المكاتب الوطنية المختلفة، فيكون للتسجيل الدولي وفقا لاتفاق مدريد نفس الأثر في جميع البلدان المتعاقدة المعنية، كما لو أن العلامة التجارية قد تم تسجيلها مباشرة أمام المكاتب الوطنية لتلك البلدان. The existence of an effective international trademarks registration system plays a vital role in protecting these marks and promoting economic development and legitimate competition at the national and international levels, so that the protection of such marks is not limited to the territory of the country in which they are registered, but extends to many countries internationally. Hence the Madrid Agreement on International Registration of Trademarks of 1891, the provisions of which are based on the Paris Convention for the Protection of Industrial Property, provides the possibility of obtaining the protection of trademarks in various Contracting States by depositing a single international application with the International Office of the Organization. "WIPO", which registers and publishes such registrations, communicates them to the Contracting Parties, replacing a full range of procedures and formalities in the various national offices, and international registration in accordance with the Madrid Agreement has the same effect in all the Contracting Countries concerned, as if the trademark had been registered directly to the national offices of those countries.
Keywords: التنمية الاقتصادية -- العلامات التجارية -- الاتفاقيات الدولية -- حقوق الملكية -- الحماية القانونية